Preparation of 5-methylfurfural from starch in one step by iodide mediated metal-free hydrogenolysis. Issue 15 (17th July 2019) - Peng, Yang; Li, Xianghua; Gao, Tian; Li, Teng; Yang, Weiran
Abstract : Starch is available in large quantities and at cheap price, especially that from stale rice, root and tuber crops, etc. A metal-free approach to convert starch to 5-methylfurfural using HCl, NaI and H2 in a biphasic solvent system has been developed. Abstract : Starch is available in large quantities and at cheap price, especially that from stale rice, root and tuber crops, etc ., which makes it desirable for conversion to value-added products. A metal-free approach to convert starch to 5-methylfurfural (5-MF) using hydrochloric acid, sodium iodide and hydrogen in a biphasic solvent system has been developed. 5-MF is an important fine chemical, widely used in food, medicine, pesticides, cosmetics and other industries, and is also considered to be an important bio-gasoline precursor. I − has superior nucleophilic substitution properties and high reactivity towards C–O bond cleavage, which is crucial for this transformation. Under optimal reaction conditions, 38.0% of 5-MF and 45.6% of total organic products can be obtained from starch with 22.5% levulinic acid as the main side product. Besides, 80.8% 5-MF can be directly obtained from 5-hydroxymethylfurfural (HMF) through the same process. To the best of our knowledge, this is the first reported example of a metal-free process to convert starch and HMF directly to 5-MF. The reaction mechanism was well studied. The catalyst system was proved to be stable and was recycled five times without loss of activity.